Lung Function Can Predict the Expected Inspiratory Airflow Rate through Dry Powder Inhalers in Asthmatic Adolescents - Roberto Walter Dal Negro; Paola Turco; Massimiliano Povero (MDPI AG, 2022)
Several factors affect drug delivery from dry powder inhalers (DPIs). Some are related to patient's physiological characteristics, while others depend on DPIs' technical aspects. The patient's inspiratory airflow rate (IAR) affects the pressure drop and the turbulence needed to disaggregate the powder inside a DPI. The present study investigated whether lung function limitations occurring in asthmatic adolescents affect their IAR when inhaling through a DPI simulator. Eighteen consecutive adolescents with asthma were recruited, and IAR was randomly assessed at low-, mid-, and high-resistance regimens. A multiple logistic model was developed to evaluate the association of patients' lung function characteristics and devices' resistance with the probability to achieve the expected IAR (E-IAR). The mean value of E-IAR achieved seemed to be sex- and age-independent. Low- and high-resistance regimens were less likely to consent the E-IAR level (odds ratio [OR] = 0.035 and OR = 0.004, respectively). Only the basal residual volume and the inspiratory resistance, but not the Forced Expiratory Volume in 1 s (FEV1), seemed to affect the extent of IAR in asthmatic adolescents (OR = 1.131 and OR = 0.290, respectively). The results suggest that the assessment of current lung function is crucial for choosing the proper DPI for asthmatic adolescents.